2014
DOI: 10.1007/s10008-014-2658-x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and stability study of potassium ferrate (VI) coated with phthalocyanine for alkaline super-iron battery

Abstract: The potassium ferrate (VI) coated with phthalocyanine (H 2 Pc) was successfully prepared via a facile coprecipitation process. Scanning electron microscopy and Fourier transform infrared spectrum revealed that K 2 FeO 4 had been coated with H 2 Pc particles. When evaluated as cathodic material for alkaline super-ion battery, the effects of H 2 Pc coating on the electrochemical stability of K 2 FeO 4 electrodes upon prolonged immersion time were investigated by galvanostatic discharge test, open-circuit potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Stabilization of ferrate(VI) electrodes was also achieved by coatings with phthalocyanines, and porphyrines . K 2 [FeO 4 ] was dispersed in an organic solvent previously loaded with the dye by ultrasonical vibration, and the solvent was removed in a vacuum.…”
Section: The Chemistry Of Ferrates(vi)mentioning
confidence: 99%
“…Stabilization of ferrate(VI) electrodes was also achieved by coatings with phthalocyanines, and porphyrines . K 2 [FeO 4 ] was dispersed in an organic solvent previously loaded with the dye by ultrasonical vibration, and the solvent was removed in a vacuum.…”
Section: The Chemistry Of Ferrates(vi)mentioning
confidence: 99%
“…More work is needed to study the effect of the coexisting ions and the type of buffers used on the stabilization of ferrate compounds in solid state or aqueous solution [16]. Walz et al [17] investigated the stabilization of BaFeO 4 materials by nanoporous silica coatings and showed that these coatings * Baohui Wang wangbh@nepu.edu.cn stabilize BaFeO 4 when stored in air and, to a lesser degree, electrolyte solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [18] investigated that the Y 2 O 3 -ZrO 2 composite coatings were used to greatly improve the stability and charge transfer properties of K 2 FeO 4 cathodes in an alkaline electrolyte relative to the uncoated cathode. More research [16,19,20] combined the use of organic compounds and inorganic materials to coat K 2 FeO 4 to improve the stabilization of ferrate in recent years. In this study, it was found that FeO 4 2− in water was stabilized by the addition of KIO 4 as coexisting oxidized ions and buffers.…”
Section: Introductionmentioning
confidence: 99%
“…The protective coatings enabled the separation of the electrolyte and K 2 FeO 4 for a reduction of destroying the K 2 FeO 4 with a relative lift of the charge transfer ability. However, the mixed compounds still indicated a comparative conduct with a low stability [23,24,27,2931]. For the improvement, poly(3-hexylthiophene)-coated K 2 FeO 4 was prepared to enhance the capacity and stability of K 2 FeO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…For the stability of the ferrate solution, more works have been presented to study the effect of the coexisting ions and buffers on the stabilization in the aqueous solution [24]. The decomposition rate of the ferrate solutions depends strongly on the initial ferrate concentration, coexisting ions, pH and temperature of the solution [5,14,25].…”
Section: Introductionmentioning
confidence: 99%